Developing An Inclusive Culture Through “Utari Sendakeb” At UPT SD Negeri 263 Gresik - Badrut Tamam; Yatim Riyanto; Erny Roesminingsih (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
One of the efforts to create a comfortable and friendly school social environment at the Inclusive Education Provider School (SPPI) is to develop an inclusive culture at the school. In fact, an inclusive culture at UPT SD Negeri 263 Gresik has not materialized or has not been developed properly. This is indicated by the continued bullying attitude towards Children with Special Needs (ABK) by regular students and some students do not want to associate or interact with ABK. This study aims to identify and describe the inclusive culture developed by UPT SD Negeri 263 Gresik through